Retrieving Mark Anthony and Cleopatra by means of the coins - Silva, Camilla Ferreira Paulino da (Romanitas - Revista de Estudos Grecolatinos, 2014)
This article aims at discussing the discursive potential of coins to recover less known versions of famous characters, such as Cleopatra and Mark Anthony. We selected a set of coins, minted throughout the consorts' lives, to highlight how coins fulfilled a rhetorical request amid a contentious period (the 40’s and 30’s B.C). Thus, despite the difficulties in retrieving Anthony and Cleopatra’s discourse, for they lost the Battle of Actium (31 B.C.) and were negatively represented by the Literature, we demonstrate how coins helped to propagate representations that the couple created for themselves (individually and jointly), in accordance with the political debate of that time.
Keywords: Coins; Cleopatra; Mark Anthony; Representation